PENGARUH KERAGAMAN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PERUSAHAAN KECAP SEGI TIGA DI KABUPATEN MAJALENGKA - Wawan Yuswanto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Marketing is the main factor as the company's strategy in running its business, especially those related to consumers. The word marketing itself comes from the word market, or it can also be interpreted as a mechanism that brings together sellers and buyers so that a supply and demand process occurs. Decisions about product placement are related to the availability of products / product diversity in the right amount and in the right location (Tjiptono, 2014). The more diverse the number and types of products sold in one place, the consumer will feel satisfied if he makes a purchase at that place and he does not need to make a purchase elsewhere. And he will repeat the same thing for the next purchase. Quality has a very important meaning in consumer purchasing decisions. If the quality of the product produced is good, consumers tend to make repeat purchases, while if the quality of the product is not as expected, consumers will divert their purchases to other similar products. Often, consumers' minds are already imprinted that certain company's products are much higher quality than competitors' products and consumers will buy products they believe are of higher quality. Although consumers have different perceptions of product quality, at least consumers will choose products that can satisfy their needs. Purchasing decisions are consumer decisions regarding preferences for brands in the choice set (Kotler and Kler, 2016: 240). Another definition of purchasing decision is the buyer's decision about which brand to buy (Kotler and Armstrong, 2018: 181).